SYMPTOMATOLOGY, COMPLICATIONS AND MODERN LABORATORY DIAGNOSTIC METHODS OF DIAGNOSIS OF ATYPICAL FORMS OF MYOCARDIAL INFARCTION - Toshpulatov Sardorjon Sarvar o‘g‘li; Abduraupov Diyorbek Zafar o‘g‘li; Adilbekova Dilorom Bakhtiyarovna (Scholars Digest Publishing, 2024)
Myocardial infarction (MI) is the term used for the event of a heart attack, which is damage to the heart muscle due to reduced blood flow and lack of oxygen to the heart due to the formation of plaque on the inner walls of the arteries. Myocardial infarction symptoms include chest pain from the left arm to the neck, shortness of breath, sweating, nausea, vomiting, abnormal heartbeat, anxiety, fatigue, weakness, stress, depression, and more. factors include. Myocardial infarction is a limited necrosis of the heart muscle and occurs as a result of an acute imbalance between its blood supply and demand. This article talks about the clinical picture of myocardial infarction, types of myocardial infarction, clinical periods, early and late complications, measures aimed at prevention and treatment.
Keywords: Myocardial infarction, prodromal (period before infarction), scarring (period after myocardial infarction), early and late complications, arrhythmic and asthmatic types.